If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3(2x + -8) = 8x + -40 Reorder the terms: 4x + 3(-8 + 2x) = 8x + -40 4x + (-8 * 3 + 2x * 3) = 8x + -40 4x + (-24 + 6x) = 8x + -40 Reorder the terms: -24 + 4x + 6x = 8x + -40 Combine like terms: 4x + 6x = 10x -24 + 10x = 8x + -40 Reorder the terms: -24 + 10x = -40 + 8x Solving -24 + 10x = -40 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -24 + 10x + -8x = -40 + 8x + -8x Combine like terms: 10x + -8x = 2x -24 + 2x = -40 + 8x + -8x Combine like terms: 8x + -8x = 0 -24 + 2x = -40 + 0 -24 + 2x = -40 Add '24' to each side of the equation. -24 + 24 + 2x = -40 + 24 Combine like terms: -24 + 24 = 0 0 + 2x = -40 + 24 2x = -40 + 24 Combine like terms: -40 + 24 = -16 2x = -16 Divide each side by '2'. x = -8 Simplifying x = -8
| 4.5x-3.8y+6.9x-0.2y= | | 2s+7=10s-7 | | 27+2x+3=5x | | 2s+7=10-7 | | X^2-2x+4=-8x-4 | | 5x+63=7(x-9) | | n-7=13 | | x+2/3= | | x^2-2x=21 | | X^2-4x+5=10 | | -5(3x+7)=-15 | | 7x-9=2x+21 | | 3x-9y-8x+7y= | | x+2= | | x^2+2x=19 | | 6(5z-1)-4(z+6)=3(z+1) | | X^2-10+16=0 | | 4(x+2)-6=2x-7 | | 2x-3=5x+12 | | -3x-9=-2x-7 | | 3(5r+5)-4(r-3)= | | 260+40x= | | 4a+7b= | | 2x-3=3x-6 | | 100-8+677543-3= | | 4x^2-15x+9=-8x+6 | | 3(2x+5)+4(3x+2)=104 | | x^2-12x+6=0 | | 4(-1+2)-6=2x-7 | | 3x+5=-4x-9 | | 27x^2-12=0 | | 2x+54=8x-6 |